MANAGEMENT RECOMMENDATIONS OF NURSE SHARK POPULATION (Ginglymostoma cirratum), ON CABO BLANCO ABSOLUTE NATURE RESERVE (Biocenosis, 2014)
Reproduction of free living Nurse Shark in shallow waters is very stable in their frequent of observation at Cabo Blanco Reserve, these mean it can be used as a resource management to ensure its conservation and ecotourism as an sustainable alternative if it is done correctly. This paper brings together the key recommendations for an appropriate low impact visitation.
Keywords: Sharks; Ecotourism; Sexual behavior; Visiting rules